Optimization of parameters for the Fe-humic acid complex formation using flourescence spectroscopy. - Araniador, Glaicyl Dame Ann B. (2019.)
Humic acid was extracted from an artesian well located at Sta. Barbara, Iloilo. It was black in color and had a powdery texture after oven-drying. Humic acid samples were used to prepare complexes with 〖Fe〗^(3+) ions to determine the ideal conditions to maximize the binding of the metal ion. Using the fluorescence data of the ligand as a comparative measure to confirm complex formation, varying concentration and pH conditions were used in preparing Fe-HA complexes. The excitation spectra of the different concentration ratios prepared showed that pH 6 favored the complex formation. The emission spectra showed that pH 6 exhibited high fluorescence signals. The EEMs of different concentration ratios at pH 6 showed that it is the optimal range for complex formation. In pH 8 and pH 10, no consistent pattern in their EEMs can be observed. This indicates that alkaline conditions, complex formation is not favored.
Thesis (Undergraduate, Bachelor of Science in Chemistry) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo. 2019.
Keywords: Fe-HA complex; Flourescence